Effect of In, Ce and Bi dopings on sintering and dielectric properties of Ba(Zn1/3Nb2/3)O3 ceramics - Mergen, A.; Korkmaz, E. (Elsevier BV, 2011)
Abstract In, Ce and Bi doped Ba(Zn1/3Nb2/3)O3 (BZN) ceramics were prepared by conventional mixed oxide technique. In doping between 0.2 and 4.0 mol% increased the density of BZN at 1300 °C, Ce doping caused a decrease in density at 1250 °C. Levels of Bi2O3 up to 1.0 mol% had negative effect on densification, while high level doping could significantly improve the densification of the specimens. XRD of the samples indicated that In, Ce and Bi doping resulted in single phase formation at all concentrations, except 0.5 mol% Bi. SEM of Bi doped BZN indicated only single phase structure and Ce doping even at 0.2 mol% gave some secondary phases. In and Ce doping increased the dielectric constant from 41 to around 66 at 1 MHz. Bi doping decreased the dielectric constant to about 37 at 0.2 mol%, and then higher doping led to dielectric constant to increase to about 63.